Integrasi Nilai Pancasila dalam Sistem Hukum Konstitusi Indonesia: Implikasi terhadap Perlindungan Hukum Adat - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Dini Agustin Rahmawati; Zahwa Luthfi’a Az-zahra; Nadia Shafira (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the integration of Pancasila values in the Indonesian constitutional legal system and its implications for the protection of customary law. Pancasila as the basis of the state and the source of all sources of law in Indonesia plays an important role in shaping applicable legal norms. In the context of customary law, the values of Pancasila must be reflected in legislation and policies governing indigenous peoples. This article highlights the importance of a comprehensive understanding of Pancasila values to ensure indigenous peoples’ rights are protected in a fair and sustainable manner. This research uses a normative juridical approach by analyzing relevant laws and regulations, literature studies, and legal documents. The results of the study show that although there has been formal recognition of customary law in the constitution and various laws, its implementation still faces challenges, especially related to conflicts of interest between the interests of the state, the market, and indigenous peoples. This article concludes that the integration of Pancasila values in the constitutional legal system should be strengthened through more inclusive and equitable policies, as well as more effective legal protection mechanisms for indigenous peoples.